2021
DOI: 10.3389/fphy.2021.636001
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Tumor Microenvironment pH During Radiotherapy Using a Novel Cerenkov Emission Multispectral Optical Probe Based on Silicon Photomultipliers

Abstract: Cerenkov Emission (CE) multispectral analysis with silicon photomultiplier (SiPM)-based optical probes is a promising tool for online tumor microenvironment interrogation and targeting during radiotherapy delivery. With the extreme sensitivity of SiPMs, deep tissue multispectral CE measurements can be realized in a clinical setting. In this work, we utilize our Cerenkov Emission Multi-spectral Imaging (CMSI) prototype probe to interrogate the spectral components of the CE signal generated during external beam … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…25 In a previous study, Oraiqat et al demonstrated the potential of Cherenkov multispectral imaging as a method for measuring pH changes in vitro using phenol red as a contrast agent. 26 The introduction of a few millimeters thick FXG film on the surface of the human body will enhance the dose received by the skin and potentially modify the delivery to the target area. Further research is needed to comprehensively understand the specific impact of incorporating an FXG film into treatment planning.…”
Section: Discussionmentioning
confidence: 99%
“…25 In a previous study, Oraiqat et al demonstrated the potential of Cherenkov multispectral imaging as a method for measuring pH changes in vitro using phenol red as a contrast agent. 26 The introduction of a few millimeters thick FXG film on the surface of the human body will enhance the dose received by the skin and potentially modify the delivery to the target area. Further research is needed to comprehensively understand the specific impact of incorporating an FXG film into treatment planning.…”
Section: Discussionmentioning
confidence: 99%